Silver Nanoparticles Biosynthesized from Vaccinium myrtillus L. against Multiple Antibiotic Resistance and Biofilm Forming Escherichia coli and Pseudomonas aeruginosa - Ildiz, Nilay; Korkmaz, Firdevs; Yusufbeyoğlu, Sadi; Kilic, Ayşe Baldemir; Ocsoy, İsmail (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: Despite new innovations and process improvements, biofilm forming bacterial infections still pose a serious threat to patients. Silver nanoparticles (AgNPs) have been shown to have antibacterial properties and have been applied for surface manufacturing of many permanent medical devices at the same time. Therefore, we attempted to compare the performance of green synthesis of AgNPs and Vaccinium myrtillus L. plant extracts in terms of antibacterial and antibiofilm potential against multi drug resistant (MDR) biofilm forming Pseudomonas aeruginosa and Escherichia coli clinical strains. Materials and Methods: The biosynthesized AgNPs were characterized by UV-Visible spectroscopy. The antibacterial activity of the nanoparticles was determined by using disc diffusion and broth micro dilution method. Antibiofilm properties of nanoparticles have also been investigated by using scanning electron microscopy (SEM) and tissue culture plate (TCP) method. Results: Both extract and AgNP showed comparable bactericidal (p<0,0001) and antibiofilm activity (p<0,0001), but the mode of bacterial interaction and the degree of damage were completely different. Conclusion: For the first time with this study, extracts and also nanoparticles obtained from V. myrtillus were found to be effective in strains that have high biofilm activity and multiple drug resistance. Biosynthesized AgNPs were found to reduce planktonic cells as well as biofilm growth in a dose dependent manner. The results also supported the antibiofilm potential of AgNPs. This finding thus provides an idea of the development of silver nanoparticle-based biomaterials for use as effective surface modifying agents
Keywords: E. coli; P. aeruginosa; Biofilm; Vaccinium myritillus; Nanoparticle